Rapid phase-controlled microwave synthesis of nanostructured hierarchical tetragonal and cubic beta-In2S3 dandelion flowers - Naik, S. D.; Jagadale, Tushar C.; Apte, S. K.; Sonawane, S.; Kulkarni, M. V.; Patil, S. I.; Ogale, Satishchandra B.; Kale, B. B. (Chemical Physics Letters, 2008)
Phase controlled synthesis of hierarchical nanostructured beta-In2S3 dandelion flowers is realized by a rapid microwave solvothermal process using indium metal, nitric acid and thiourea as precursors. The tetragonal and cubic phases of the compound have been successfully and separately stabilized in the same type of dandelion morphology by using aqueous-mediated and methanol-mediated synthesis, respectively. The possible mechanism responsible for phase control is discussed. Optical properties of the flowers as well as their hydrogen generation capability by photodecomposition of H2S under visible light are also reported. (c) 2007 Elsevier B.V. All rights reserved.

Cobalt nanoparticles doped emaraldine salt of polyaniline: a promising room temperature magnetic semiconductor - Hatamie, Shadie; Kulkarni, M. V.; Kulkarni, S. D.; Ningthoujam, R. S.; Vatsa, R. K.; Kale, Sangeeta N. (Journal of Magnetism and Magnetic Materials, 2010)
Incorporation of magnetic nanoparticles in polymers with organic functional groups working as semiconducting substrate is of immense interest in the field of dilute magnetic semiconductors (DMS) and spintronics. In this article we report on synthesis and evaluation of dilutely doped (0-10 wt%) cobalt nanoparticles in emaraldine salt (ES) of polyaniline in the presence of dodecyl benzene sulfonic acid (DBSA) and p-toluene sulfonic acid (p-TSA) using a sonochemical-assisted-reduction approach as a possible DMS candidate. The X-ray diffraction pattern and high resolution transmission electron microscopy (HRTEM) image show the ES to be polycrystalline, in which 10 nm sized Co nanoparticles get embedded in its FCC structural form. From Fourier transform infrared (FT-IR) and UV-visible (UV-vis) spectroscopy studies, it is predicted that cobalt particles get electrostatically bound to the specific SO(3)(-) ion sites of ES, thereby modifying torsional degrees of freedom of the system. The applied field dependent magnetization study shows that the sample exhibits hysteresis loop with a minimal doping of 3 wt% of Co nanoparticles and increases with the amount of Co nanoparticles in ES due to dipolar interaction. The electron transport data show that with increase in Co wt% there is a gradual shift from ohmic to non-ohmic response to the sample bias, accompanied by opening of electrical hysteresis and an increased resistance. The non-linear response of higher doped systems has been attributed to the combination of direct and Fowler-Nordheim tunneling phenomena in these systems. Persistence of optical and transport properties of the polymer, with an introduction of magnetic moment in the system, envisages the system to be a fine magnetic semiconductor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cobalt nanoparticles; Magnetic semiconductor; polyaniline